Soil the incredible story of what keeps the earth, and us, healthy - Evans, Matthew, 1966- (Murdoch Books, 2021)
What we do to the soil, we do to ourselves. Soil is the unlikely story of our most maligned resource as swashbuckling hero. A saga of bombs, ice ages and civilisations falling. Of ancient hunger, modern sicknesses and gastronomic delight. It features poison gas, climate collapse and a mind-blowing explanation of how rain is formed. For too long, we've not only neglected the land beneath us, we've squandered and debased it, by over-clearing, over-grazing and over-ploughing. But if we want our food to nourish us, and to ensure our planet's long-term health, we need to understand how soil works - how it's made, how it's lost, and how it can be repaired. In this ode to the thin veneer of Earth that gifts us life, commentator and farmer Matthew Evans shows us that what we do in our backyards, on our farms, and what we put on our dinner tables really matters, and can be a source of hope. Isn't it time we stopped treating the ground beneath our feet like dirt?